Dietary Intervention Induced Distinct Repercussions in Response to the Individual Gut Microbiota as Demonstrated by the In Vitro Fecal Fermentation of Beef - Vineet Singh; Youn-Chul Ryu; Tatsuya Unno (Applied Sciences, 2021)
Animals and humans have very different gut microbiota, and the human microbiota is unique to each individual. For these reasons, it is difficult to find a diet that provides all the nutrients according to individual requirements. In this study, we investigated the possibility of using simple in vitro fecal fermentation of digested food to evaluate fundamental differences in the gut metabolism of individuals with different microbiomes in response to specific dietary interventions. We fermented beef using six human fecal microbiotas, analyzed shifts in these microbiomes, and quantified short-chain fatty acid (SCFA) production in each system. Our results demonstrate that each microbiome responds with a unique shift in composition, SCFA production, and metabolic activity following 90 min of fecal fermentation of beef. Differentially abundant genera and metabolic activities varied among subjects. Only two subjects’ fecal microbiome showed no significant changes in their metabolic activity, while the other subjects’ microbial metagenome showed anywhere between 17 and 60 differences in their metabolism, including several changes associated with heart disease (i.e., depletion of oleate and palmitoleate biosynthesis). This study revealed the varying responses of each microbiome when exposed to digested beef, suggesting that this method could provide fundamental information in understanding personal nutrient requirements and the impact of changes in the individual gut microbiota on human health. Although further studies using larger study populations are required, this study describes a simple and cost-effective protocol for evaluating the interactions between specific dietary interventions and individual gut microbiota differences.